Relationship between species distribution of sandy alpine grasslands and microtopography in the source regions of Yangtze river - Zhao, Peng; Xu, Xianying; Tang, Jinnian; Jiang, Shengxiu (Frontiers in Environmental Science, 2022)
Dynamic of sandy alpine grasslands affect the progress and reversal of desertification in source regions of the Yangtse Rivers. To understand geomorphic driving mechanism of species distribution pattern, we examined the species compositions and delineated the most important landform factors influencing species distribution of sandy alpine grassland using two-way indicator species analysis (TWINSPAN), detrended correspondence analysis (DCA), and canonical correspondence analysis (CCA). Field survey were conducted in summer of 2016 using stratified random methods in hilly sloped lands, floodplains, foothills, and valley land of study region. In total, 29 plant species grouped into 27 genera and 16 families were identified. Leymus secalinus, Elymus dahuricus and Corispermum declinatum are the dominant species of sandy alpine grassland communities in different microtopography. The present vegetation reflected xerosere character, which indicated that desertification of alpine grassland is in progress. Standard frequency distribution of species varied with different microtopography, the proportion of dominant species was generally lower than rare species, and the vegetation community was in a highly successional stage. Seven groups were distinguished through TWINSPAN, distribution of which in the DCA ordination graph showed species with similar ecotype is clustered together. The results of the CCA ordination revealed that slope and aspect are the dominant factors among microtopography determining the species distribution of sandy alpine grassland.